BAHASA FIGURATIF DALAM ANTOLOGI PUISI PERAHU KERTAS KARYA SAPARDI DJOKO DAMONO DAN PEMANFAATANNYA SEBAGAI PENGAYAAN - Adiwijaya, Satria Nugraha (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2022)
This study aims to (1) describe the form and function of figurative language in Perahu Kertas poetry anthology by Sapardi Djoko Damono, (2) describe the use of figurative language in Perahu Kertas poetry anthology by Sapardi Djoko Damono as literary enrichment material in class X senior high school. The analytical method used is descriptive semiotic analysis through heuristic and hermeneutic readings to reveal stylistic aspects and comparative analysis to describe the use of figurative language in the Perahu Kertas poetry anthology by Sapardi Djoko Damono as enrichment. The results of the study based on data analysis showed (1) the figurative language found was dominated by figure of speech and idioms with a limited number. The function of the figure of speech that was found, namely as the creation of aesthetic effects and comparison of meanings (2) the figurative language in the Perahu Kertas poetry anthology by Sapardi Djoko Damono as literary enrichment material in class X SMA is divided into two activities, namely exploratory and process skills.